The Influence of Social Media Friendship on Brand Awareness and Purchase Intention: Evidence from young adult consumers - Bilgin, Yusuf (2020)
The aim of this study is to analyze the impact of social media friendships on young adult consumers’ approach to brands in terms of awareness, image, trust, and purchase intention among. The quantitative research method was used in this study, the population of which consisted of students who were studying at undergraduate level in Turkey and who use either Facebook, Instagram, or Twitter actively. In this study, the convenience sampling method was used. Research data was collected from 1069 undergraduate students through online questionnaires on Facebook, Instagram and Twitter. The data obtained were analyzed using Structural Equation Modeling. The results of the analysis showed that social media friendships among young adult consumers had a positive impact on brand awareness, brand image, brand trust and purchasing intentions. In addition, brand awareness was found to have a strong impact on brand image and brand trust among young adult consumers. However, brand trust was more influential on the purchase intention of young adult consumers than brand image and brand awareness.